1998
DOI: 10.1007/bf03401756
|View full text |Cite
|
Sign up to set email alerts
|

High Concentration of L-Arginine Suppresses Nitric Oxide Synthase Activity and Produces Reactive Oxygen Species in NB9 Human Neuroblastoma Cells

Abstract: Hereditary argininemia manifests as neurological disturbance and mental retardation, features not observed in other amino acidemias. The cytotoxic effect of a high concentration of L-arginine (L-Arg) was investigated using NB9 human neuroblastoma cells (NB9), which express neuronal nitric oxide synthase (nNOS). When the concentration of L-Arg in the medium increased from 50 microM to 2 mM after incubation for 48 hr, the intracellular concentration of L-Arg increased from 68.0 +/- 1 pmol/10(6) cells to 1310.0 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Incubation of the cells with 0.5 mM H 2 O 2 for 24 hours leads to deterioration of viability rate, which can be reversed by an increase in arginine concentration up to one mM. Remarkably, arginine itself demonstrates cytotoxic properties in concentrations greater than one mM ( figure 6c ), which accords with the current literature ( Todoroki et al 1998 ). It was demonstrated that high concentrations (more than one mM) of L-Arginine induce severe DNA damage and arrest at the GI phase.…”
Section: Resultssupporting
confidence: 89%
“…Incubation of the cells with 0.5 mM H 2 O 2 for 24 hours leads to deterioration of viability rate, which can be reversed by an increase in arginine concentration up to one mM. Remarkably, arginine itself demonstrates cytotoxic properties in concentrations greater than one mM ( figure 6c ), which accords with the current literature ( Todoroki et al 1998 ). It was demonstrated that high concentrations (more than one mM) of L-Arginine induce severe DNA damage and arrest at the GI phase.…”
Section: Resultssupporting
confidence: 89%
“…30,42 In another, the iron oxide nanoparticle is terminated with arginine with guanidinium groups (iron oxide-arginine) that induces high cell uptake via a nonendocytic approach and excess arginine has the ability to induce ROS by modifying the cellular nitric oxide synthesis pathway and also to deplete intracellular adenosine triphosphate (ATP). 38,43,44 The zinc oxide nanoparticle is selected due to its crystal defectdependent ROS generation property. 32 This nanoparticle is also terminated with primary amines (zinc oxide-amine) to further enhance its ROS generation property.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This L-citrulline binds to the L-arginine binding site of nitric oxide synthase (NOS), inhibits nitric oxide synthesis, and functions as a NADPH oxidase to produce reactive oxygen species. 44 We further investigated the origin of autophagy induction by carbon-trehalose. Trehalose is known to induce autophagy via the mTOR independent pathway 45 and also known to activate transcription factor EB (TFEB) or lysosome biogenesis factor, which in turn can induce autophagic flux.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The authentic primer for iNOS was 5'-GTGAGGATCAAAAACTGGGG-3' and the antisense primer was 5'-ACCTGCAGGT TGGACCAC-3'. The authentic primer for eNOS was 5'-CACTGAGATCGGCACGA-GGA-3' and the antisense primer was 5'-GTCACCATCGTGGACCACCA-3' [17]. The authentic sense primer for HO-1 was 5'-GAATTCAGCATGCCCCAGGATTTG-3' and the antisense primer was 5'-TCTAGACTAGCTGGATGTTGAGCAGGA-3' [18].…”
Section: Methodsmentioning
confidence: 99%